Bond behavior of carbon fabric reinforced cementitious matrix (FRCM) composites considering matrix impregnation. (15th April 2021) - Zhu, Miaochang; Zhu, Ji-Hua; Ueda, Tamon; Matsumoto, Koji; Su, Meini
Abstract: This paper presents an investigation on the bond behavior of the carbon fabric-cementitious matrix interface within the fabric reinforced cementitious matrix (FRCM) composite. The embedded carbon yarn shows a complicated bond behavior due to stochastic and incomplete impregnation of the matrix and can be subdivided into the outer (impregnated) and inner (non-impregnated) parts. Pullout tests were carried out on the carbon FRCM composite aiming at examining the effect of matrix impregnation on the bond behavior between fabric and matrix. The test results show that pullout specimens with a 30 mm embedded length failed due to pure slippage of the carbon yarn, while the failure became the slippage and partial rupture of the carbon yarn for the specimens with longer lengths. The impregnated filaments are estimated as about 30% of the total filaments within an embedded carbon yarn according to image processing and analysis results. Different bond slip relationships were assumed and evaluated for the outer and inner parts within an embedded carbon yarn based on pullout test results. The accuracy of the evaluated bond slip relationships was validated through a good agreement between experimental results and finite element modeling.